Understanding Culture: A Literature Review Comparing Three Cultural Pedagogies - Tabitha Kidwell (Register Journal, 2017)
ENGLISH ABSTRACT Culture is an integral part of language study, but the field has yet to put forward a coherent theoretical argument for how culture can or should be incorporated in language education.  In an effort to remedy this situation, this paper reviews literature on the teaching of culture, drawing on Larzén’s (2005) identification of three pedagogies used to teach about culture within the language classroom:  through a pedagogy of information, a pedagogy of preparation, and a pedagogy of encounter.  The pedagogy of information takes a cognitive orientation, framing culture as factual knowledge, with a focus on the teacher as the transmitter of knowledge.  The pedagogy of preparation portrays culture as skills, and aims to help students develop the sociocultural, pragmatic, and strategic competence necessary for interactions with native speakers.  The pedagogy of encounter takes an intercultural approach, with an affective orientation, and aims to help students develop tolerance, empathy, and an awareness of their own and others’ perspectives, and the emergent nature of culture. Using these three pedagogies as a conceptual framework, this paper reviews scholarship in support and critique of each type of cultural teaching.  Because each of these three pedagogies continues to be used in various contexts worldwide, a clear understanding of the beliefs systems underpinning the belief systems of teachers and learners is essential. Keywords:  Culture; Language Teaching; Methodologies. INDONESIAN ABSTRACTBudaya merupakan bagian integral dari studi bahasa, namun khalayak belum mengemukakan argumen teoritis yang koheren untuk bagaimana budaya dapat atau harus digabungkan dalam pendidikan bahasa. Dalam upaya memperbaiki situasi ini, makalah ini mengulas literatur tentang ajaran budaya, dengan mengacu pada identifikasi tiga pedagogi Larzén (2005) yang digunakan untuk mengajarkan tentang budaya di dalam kelas bahasa: melalui pedagogi informasi, pedagogi persiapan, dan pedagogi perjumpaan Pedagogi informasi mengambil orientasi kognitif, membingkai budaya sebagai pengetahuan faktual, dengan fokus pada guru sebagai pemancar pengetahuan. Pedagogi persiapan menggambarkan budaya sebagai keterampilan, dan bertujuan untuk membantu siswa mengembangkan kompetensi sosiokultural, pragmatis, dan strategis yang diperlukan untuk interaksi dengan penutur asli. Pedagogi pertemuan mengambil pendekatan antar budaya, dengan orientasi afektif, dan bertujuan untuk membantu siswa mengembangkan toleransi, empati, dan kesadaran akan perspektif mereka sendiri dan orang lain, dan sifat budaya yang muncul. Dengan menggunakan ketiga pedagogi ini sebagai kerangka konseptual, makalah ini mengulas pustaka untuk mendukung dan mengkritik setiap jenis pengajaran budaya. Karena masing-masing dari ketiga pedagogi ini terus digunakan dalam berbagai konteks di seluruh dunia, pemahaman yang jelas tentang sistem kepercayaan yang mendasari sistem kepercayaan guru dan pelajar sangat penting.Kata kunci: Budaya; Pengajaran Bahasa; Metodologi.